Post-Divorce Child Custody Rights in Mixed Marriages: Analysis of Supreme Court Decision Number 804K/Pdt/2016 - Galih Nur Rohmah, Fayza; Arum Prastyanti, Rina (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this study is to help regulate child custody after divorce between couples where one is an Indonesian Citizen (WNI) and the other is a Foreign Citizen (WNA). This study involves juridical to conduct normative legal research. Legislation, court decisions, and related literature are used as data sources. Reviewing, describing, and interpreting the collected data is how qualitative data analysis is carried out. The results of the study indicate that the problems that arise in mixed marriages include the place of divorce lawsuits, child custody disputes, and child citizenship. Indonesian judges use Indonesian national law to resolve child custody issues from mixed divorces. Judges rely on the most important needs of the child.